Assessing probe reliability: Functional group–specific biases revealed by interactome-wide docking of general anesthetics - Dai-Bei Yang; Xiangyu Chen; E. Railey White; Thomas T. Joseph; Joseph S. Francisco (Proceedings of the National Academy of Sciences, 2026)
General anesthetics are widely used to induce reversible unconsciousness, yet their molecular mechanisms remain incompletely understood. Despite their low binding affinities and broad protein-binding promiscuity, general anesthetics still interact with neuronal proteins in a structurally selective manner. Experimentally, chemically modified probes have been used to map their protein targets. However, the biases introduced by the structural modifications of these remain unknown, raising the key question of how reliable such experiments are in capturing true anesthetic–protein interactions. In this study, we present an interactome-scale computational approach to characterize anesthetic – protein interactions using high-throughput molecular docking. We screened two families of anesthetic ligands—propofol and etomidate, as well as chemically modified analogs of each—against a set of 2,388 experimentally determined mouse neuronal protein structures. By comparing parent and modified ligands, we reveal how functional group–specific biases, introduced by chemical modifications, altering ligands engage protein environments across the interactome. Docking poses and energies identify recurrent binding-site features and quantify how small modifications reshape interaction profiles. Using 3D spatial distribution functions, we summarize local amino acid environments surrounding each ligand, providing intuitive visualizations of interaction hotspots. This analysis exposes conserved and variable elements of anesthetic recognition and clarifies how probe modifications shape observed patterns. Our results offer a statistical and structural description of anesthetic binding across an interactome, providing mechanistic insight into affinity-based protein profiling mapping biases and guiding improved probe and drug design.